Searching for Goal by Mobile Robot with Collision-Free Motion in Unknown Environment - Abdalla, Turki Y.; Al_Duboni, Seaar J. (Basrah Journal for Engineering Sciences, 2012)
Obstacle avoidance and path planning are from the most important problems in mobile robots, especially in unknown environment . In this paper, we proposed an approach for mobile robot navigation combining path planning and obstacle avoidance. Methods such as obstacle avoidance are inspired from the nature, and have been developed by fuzzy logic to train an intelligent robot in unknown environment. The model of the robot has two driving wheels and the linear velocity and azimuth of the two wheels are independently controlled using PID controller. Inputs are obtained from ultrasonic sensors mounted on it.